2017
DOI: 10.1530/eje-16-0450
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy in patients with pituitary adenoma receiving growth hormone replacement

Abstract: Selection bias explaining some of the results cannot be excluded. However, NFPA patients with GHRT had reduced overall mortality compared with the general population, and death due to malignancy was not increased. This suggests that long-term GHRT is safe in adult patients selected for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
0
29
0
3
Order By: Relevance
“…Lately, partly due to a recently published study, a growing body of evidence is showing that GH replacement therapy is associated with reduced excess mortality or normalized mortality compared to the general population [5,16]. We have shown that GH replacement therapy is associated with normalized mortality among over 400 non-functioning pituitary adenoma patients receiving or not receiving GH replacement, who were followed for 10 years [5].…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Lately, partly due to a recently published study, a growing body of evidence is showing that GH replacement therapy is associated with reduced excess mortality or normalized mortality compared to the general population [5,16]. We have shown that GH replacement therapy is associated with normalized mortality among over 400 non-functioning pituitary adenoma patients receiving or not receiving GH replacement, who were followed for 10 years [5].…”
mentioning
confidence: 87%
“…The standardized mortality ratio (SMR) of hypopituitary patients (1.8-1.9) can be compared to that of morbidly obese patients (1.6), showing the very real effect of hormonal deficiencies on life expectancy [1,2,4]. We believe that the source of the excess mortality originates from non-physiological replacement therapy, untreated deficiencies, local effects of the tumor itself, and adverse effects of tumor treatment (mostly radiotherapy) [2,[5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After final screening, data from 10 selected studies published from 2002 to 2017 were extracted for inclusion in the current analysis [12]- [21].…”
Section: Study Identificationmentioning
confidence: 99%
“…Highest mortality is among younger patients, women and patients with diabetes insipidus (4). A recent study from Sweden shows a decline in mortality in patiens optimally replaced including GH replacement therapy (5).…”
Section: Introductionmentioning
confidence: 99%